The Formation of Spiritual Life in Selected Monastic Meditations from the 17th and 18th centuries - Łukarska, Beata (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The article is an analysis of the form and content of selected monastic meditations. Coverage, whichhas become the base for the analysis, deals with various subjects. They are to testify passion, Marian andother important events from monastic life spirituality such as renewing life according to the requirementsof a monastic rule. The authors of chosen meditations represent various schools of spirituality, for example,Benedictine, Carmelite and Jesuit. The article shows the role of prayer in the formation of spirituallife of both an individual and monastic community.